Development of an integrated system for coastal waters - Pina, Pedro (2009)
This paper describes some of the needs and problems associated to assessment of coastal and estuarine problems (sediment transport and eutrophication). The development of an integrated system including EO data, local measurements with special emphasis on modeling tools, is presented as a solution for studying and helping decision making on the subject. Two pilot sites for the implementation and the present development status of the integrated system are depicted. This framework was already presented in a recent AO specific for Portugal, which is still under evaluation.